2013
DOI: 10.1523/jneurosci.1402-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Function Occur Years before the Onset of Cognitive Impairment

Abstract: To develop targeted intervention strategies for the treatment of Alzheimer's disease, we first need to identify early markers of brain changes that occur before the onset of cognitive impairment. Here, we examine changes in resting-state brain function in humans from the Baltimore Longitudinal Study of Aging. We compared longitudinal changes in regional cerebral blood flow (rCBF), assessed by 15 O-water PET, over a mean 7 year period between participants who eventually developed cognitive impairment (n ϭ 22) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(154 citation statements)
references
References 45 publications
10
144
0
Order By: Relevance
“…In interpreting our 15 O-water PET results, we propose that longitudinal decrements in rCBF in brain regions mediating higher-order cognitive processes, such as the superior temporal and medial frontal cortices, represent early signatures of failing synaptic function related to lower SPARCL1 gene expression [5254]. Conversely, brain regions showing longitudinal increases in rCBF may represent compensatory changes in neuronal activity that may be recruited to maintain normal cognitive function in at-risk individuals [5557]. In this context, it is striking that minor allele carriers of SPARCL1 show greater longitudinal increases in rCBF in the precuneus and inferior temporal cortex, which are brain regions especially vulnerable to Aβ deposition and tau accumulation, respectively [58, 59].…”
Section: Discussionmentioning
confidence: 97%
“…In interpreting our 15 O-water PET results, we propose that longitudinal decrements in rCBF in brain regions mediating higher-order cognitive processes, such as the superior temporal and medial frontal cortices, represent early signatures of failing synaptic function related to lower SPARCL1 gene expression [5254]. Conversely, brain regions showing longitudinal increases in rCBF may represent compensatory changes in neuronal activity that may be recruited to maintain normal cognitive function in at-risk individuals [5557]. In this context, it is striking that minor allele carriers of SPARCL1 show greater longitudinal increases in rCBF in the precuneus and inferior temporal cortex, which are brain regions especially vulnerable to Aβ deposition and tau accumulation, respectively [58, 59].…”
Section: Discussionmentioning
confidence: 97%
“…Evidence from a 2013 PET study suggests that those who later develop MCI demonstrate a greater increase in perfusion over time in orbitofrontal, medial frontal and anterior cingulate regions, compared to those who do not develop MCI, and that MCI converters show greater CBF decreases in parietal, temporal and thalamic regions (Beason-Held et al 2013). A 2015 study also found that, compared to cognitively stable participants, those who showed subtle cognitive decline at an 18-month follow-up demonstrated reduced CBF at baseline, most notably in the posterior cingulate cortex, an area commonly associated with AD.…”
Section: Cbf In Cognitive Riskmentioning
confidence: 99%
“…Beason-Held and colleagues recently demonstrated that resting CBF is sensitive to predict conversion to MCI [49]. Compared to individuals who remained cognitively normal, adults who later developed MCI showed hyperperfusion in orbitofrontal, medial frontal and anterior cingulate regions over time, with decreased CBF in parietal, temporal and thalamic regions.…”
Section: Resting Cbf As a Predictive Toolmentioning
confidence: 99%
“…This suggests that increases and decreases in CBF take place years before the onset of cognitive symptoms in individuals who eventually develop cognitive impairment. Most of these changes were seen in areas that reflect early AD pathology and are thought to be associated with maintaining cognitive function, suggesting a connection between early changes in CBF and AD pathology [49]. …”
Section: Resting Cbf As a Predictive Toolmentioning
confidence: 99%